Power bounded and power bounded below composition operators on Dirichlet Type spaces - Liu Yang; Ruishen Qian (AIMS Mathematics, 2021)
Motivated by [11,12], under some conditions on weighted function K, we investigated power bounded and power bounded below composition operators on Dirichlet Type spaces $ {\mathcal{D}_{K}} $.